NEM TODA PARTICIPAÇÃO É IGUAL: planejamento de recursos hídricos a partir dos níveis de empoderamento - Desirée Cipriano Rabelo (Universidade Federal do Maranhão, 2020)
In order to evaluate the democratic quality of participation in water resources planning processes (PRHs), especially in “the methods of participation”, the research takes the classic references of participation levels, particularly, the levels assumed by the multilateral organizations: Information, Consultation and Active Involvement. This was used to classify the official reports about participation methods/strategies by of five basin planning of: Doce , São Francisco, Santa Maria da Vitória and Jucu and Piracicaba, Capivari and Jundiaí rivers. The premise is that not all participation is equal and that there are increasing forms of power sharing in the government-citizen relationship. The analysis shows the trivialization of the term “participation” and the need for transparency of the objectives and scope of public participation in the PRHs and similar processes.